Arts and Health Promotion Tools and Bridges for Practice, Research, and Social Transformation - Corbin, J. Hope; Sanmartino, Mariana; Hennessy, Emily Alden; Urke, Helga Bjørnøy (Springer Nature, 2021)
This open access book offers an overview of the beautiful, powerful, and dynamic array of opportunities to promote health through the arts from theoretical, methodological, pedagogical, and critical perspectives. This is the first-known text to connect the disparate inter-disciplinary literatures into a coherent volume for health promotion practitioners, researchers, and teachers. It provides a one-stop depository for using the arts as tools for health promotion in many settings and as bridges across communities, cultures, and sectors. The diverse applications of the arts in health promotion transcend the multiple contexts within which health is created, i.e., individual, community, and societal levels, and has a number of potential health, aesthetic, and social outcomes. Topics covered within the chapters include: Exploring the Potential of the Arts to Promote Health and Social Justice Drawing as a Salutogenic Therapy Aid for Grieving Adolescents in Botswana Community Theater for Health Promotion in Japan From Arts to Action: Project SHINE as a Case Study of Engaging Youth in Efforts to Develop Sustainable Water, Sanitation, and Hygiene Strategies in Rural Tanzania and India Movimiento Ventana: An Alternative Proposal to Mental Health in Nicaragua Using Art to Bridge Research and Policy: An Initiative of the United States National Academy of Medicine Arts and Health Promotion is an innovative and engaging resource for a broad audience including practitioners, researchers, university instructors, and artists. It is an important text for undergraduate- and graduate-level courses, particularly in program planning, research methods (especially qualitative methodology), community health, and applied art classes. The book also is useful for professional development among current health promotion practitioners, community nurses, community psychologists, public health professionals, and social workers.